A Development of Game-Based Learning in Virtual Reality for Fire Safety Training in Thailand - Satapanasatien, Kodchaporn; Phuawiriyakul, Thanchanok; Moodleah, Samart (My University, 2021)
Fire incidents damaged both the economy and human life. In the past three decades, 59,387 fire incidents in Thailand approximately lost 40 billion baht and 2,076 deaths. Fire safety training methods are organized in a very limited number each year for many reasons such as training place or safety concern. We propose game-based learning for fire safety training using virtual reality technology. We create five learning lessons based on fire training contents and three playing stages (play, learn and test) that players can interact with. It behaves as a self-learning tool that can be used often and overcome the difficulty in organizing fire safety training. In addition, virtual technology simulates realistic computer graphic contents and rich interactive actions. Most importantly it offers a safe virtual environment; it extends the audience to a wide range of ages. Our game-based training is evaluated, and the result shows that fire safety knowledge is increased by 122% and 63% compared to the non-training and the traditional training respectively as well as users' satisfaction average score is exceeded 90%.
Keywords: fire safety; game-based learning; serious game; training; virtual reality